Aplicacao de metodo computacional para representacao de relevo pelo metodo de Wentworth - Da Silva, J. C P; De Biasi, M.; Flores, E. F. (My University, 1990)
This piece of work focuses the application of a computational method to obtain clinographic maps, by using C.K. Wentworth's method. The developed program to construct the clinographic maps is completely structured in Basic Language and it uses Line PC Micro-Computers. As an exercise for practical application, in this study we defined a certain region, where the topographic base map is that of Brazil, 1:250 000 scale, Marilia contour map, having as the study area the region near the city of Assis (SP). -English summary
The Wentworth method applied to construct clinographic maps, using computational programs
Keywords: clinographic map; computer program; graphic computation; relief analysis; Wentworth method; Wentworth's method; Brazil, Assis